Mimbres during the Twelfth Century Abandonment, Continuity, and Reorganization - Nelson, Margaret C. (University of Arizona Press, 2022)
During the mid twelfth century, villages that had been occupied by the Mimbres people in what is now southwestern New Mexico were depopulated and new settlements were formed. While most scholars view abandonment in terms of failed settlements, Margaret Nelson shows that, for the Mimbres, abandonment of individual communities did not necessarily imply abandonment of regions. By examining the economic and social reasons for change among the Mimbres, Nelson reconstructs a process of shifting residence as people spent more time in field camps and gradually transformed them into small hamlets while continuing to farm their old fields. Challenging current interpretations of abandonment of the Mimbres area through archaeological excavation and survey, she suggests that agricultural practices evolved toward the farming of multiple fields among which families moved, with small social groups traveling frequently between small pueblos rather than being aggregated in large villages. Mimbres during the Twelfth Century is the first book-length contribution on this topic for the Classic Mimbres period and also addresses current debates on the role of Casas Grandes in these changes. By rethinking abandonment, Nelson shows how movement by prehistoric cultivators maintained continuity of occupation within a region and invites us to reconsider the dynamic relationship between people and their land.